MENINGKATKAN KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI PERBAIKAN BERKELANJUTAN - Dibyantoro; Prahiawan, Wawan; Ramdansyah, Agus David (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this study was to examine the effect of continuous improvement organizationalculture on employee performance with work motivation and innovative work behavior asintervening variables. The research method is quantitative using a questionnaire with a Likertscale of 10 points and the sampling technique is done by simple random sampling. The numberof samples used is 100 to test the hypothesis. Structural Equation Modeling was used to test thestatistical significance of the path coefficients. The research findings explain that continuousimprovement organizational culture has a positive and significant influence on work motivationand innovative work behavior. Continuous improvement work culture and innovative workbehavior have a positive and significant impact on employee performance. Work motivation hasa positive and insignificant effect on employee performance. Continuous improvement workculture has an indirect effect on employee performance through innovative work behavior whichis greater than the direct influence of continuous improvement work culture on employeeperformance